Vertex Operator Representations of Type C_l^(1) and Product-Sum Identities - Hu, Naihong; Xia, Li-Meng (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We construct a class of homogeneous vertex representations of C_l^(1), l ≥ 2, and deduce a series of product-sum identities. These identities have fine interpretation in the number theory.